2020
DOI: 10.1111/ajad.13063
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Buprenorphine—A Treatment for Psychological Pain and Suicidal Ideation?

Abstract: Background and Objectives: Buprenorphine is commonly used to manage opioid use disorder; however, the literature describes its potential role in treating treatment-resistant depression. Methods: We present a patient with bipolar disorder and opioid use disorder, who presented status post-suicide attempt. Results: After initiating buprenorphine-naloxone, the patient reported rapid improvement in depressive symptoms, pain, and suicidal ideation. Discussion and Conclusions: This case demonstrates buprenorphineʼs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The present study showed that the rate of suicidal ideation was lower among patients treated with buprenorphine maintenance compared to other drugs. This difference was even statistically significant between the opium tincture and the buprenorphine groups of treatment, which is consistent with the findings of previous research demonstrating buprenorphine’s anti-suicidal and mood-stabilizing capabilities ( 1 , 45 - 48 ). This finding highlights buprenorphine as a treatment for depression, as well as its anti-suicidal effects.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that the rate of suicidal ideation was lower among patients treated with buprenorphine maintenance compared to other drugs. This difference was even statistically significant between the opium tincture and the buprenorphine groups of treatment, which is consistent with the findings of previous research demonstrating buprenorphine’s anti-suicidal and mood-stabilizing capabilities ( 1 , 45 - 48 ). This finding highlights buprenorphine as a treatment for depression, as well as its anti-suicidal effects.…”
Section: Discussionsupporting
confidence: 91%
“…In another case report, a patient with cannabis-induced psychotic disorder and opioid depressive disorder with severe suicidal thoughts was treated successfully with a single high dose (96 mg) of buprenorphine [ 160 ]. Another case report showed that buprenorphine/naloxone (8 mg/2 mg) was effective in reducing pain and suicidal ideation in a 39-year-old male with a history of bipolar disorder, multiple suicide attempts, and polysubstance abuse [ 161 ]. Chart reviews of suicidal adult depressed patients with comorbid chronic pain and opioid use disorder who received off-label buprenorphine also found some support for the anti-suicidal properties of buprenorphine [ 162 ].…”
Section: Introductionmentioning
confidence: 99%